Design pattern recommendations for building decentralized healthcare applications - Zhang, Peng; Kelley, Adair; Schmidt, Douglas C.; White, Jules (Frontiers in Blockchain, 2023)
Blockchain and distributed ledger technologies (DLT) are emerging decentralized infrastructures touted by researchers to improve existing systems that have been limited by centralized governance and proprietary control. These technologies have shown continued success in sustaining the operational models of modern cryptocurrencies and decentralized finance applications (DeFi). These applications has incentivized growing discussions in their potential applications and adoption in other sectors such as healthcare, which has a high demand for data liquidity and interoperability. Despite the increasing research efforts in adopting blockchain and DLT in healthcare with conceptual designs and prototypes, a major research gap exists in literature: there is a lack of design recommendations that discuss concrete architectural styles and domain-specific considerations that are necessary for implementing health data exchange systems based on these technologies. This paper aims to address this gap in research by introducing a collection of design patterns for constructing blockchain and DLTbased healthcare systems that support secure and scalable data sharing. Our approach adapts traditional software patterns and proposes novel patterns that take into account both the technical requirements specific to healthcare systems and the implications of these requirements on naive blockchain-based solutions.